Synechocystis: A model system for expanding the study of cyanobacterial circadian rhythms - Zhao, Chi; Xu, Yao; Wang, Bo; Johnson, Carl Hirschie (Frontiers in Physiology, 2023)
The study of circadian rhythms in bacteria was transformed by studies of the cyanobacterium Synechococcus elongatus. However, in a number of respects S. elongatus is atypical, and while those unusual characteristics were helpful for rapid progress in the past, another commonly used cyanobacterial species, Synechocystis sp. PCC 6803, may be more representative and therefore more productive for future insights into bacterial clock mechanisms. In the past, circadian studies of Synechocystis have suffered from not having an excellent reporter of circadian gene expression, but we introduce here a new luminescence reporter that rivals the reporters that have been used so successfully in S. elongatus. Using this new system, we generate for the first time in Synechocystis circadian period mutants resulting from point mutations. The temperature compensation and dark-pulse resetting that mediates entrainment to the environment is characterized. Moreover, we analyse the complex organization of clock genes in Synechocystis and identify which genes are essential for circadian rhythmicity and adaptive fitness for entrainment and optimal phase alignment to environmental cycles (and which genes are not). These developments will provide impetus for new approaches towards understanding daily timekeeping mechanisms in bacteria.